Management of multiple pulp necrosis in a child with periventricular leukomalacia: A case report - Evy Afiyah Syagran; Prima Nerito; Muhammad Hefdi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Periventricular leukomalacia (PVL) is a white matter lesion of the brain that can cause a variety of neurological disorders, including mental retardation and communication disorders. This condition often presents challenges in dental care due to the patient's limited ability to communicate and cooperate during dental procedures. Purpose: To address the management of multiple pulp necrosis in a child with periventricular leukomalacia. Method: A patient presented with a history of PVL, accompanied by mental retardation and communication disorders. Clinical and diagnostic examinations revealed severe pain with a high pain score, requiring comprehensive management. Given the patient's limited cooperation and the complexity of the procedure, treatment was performed under general anesthesia. The procedure included eliminating the source of infection, preserving the remaining teeth, and extracting teeth with poor prognosis. The entire procedure was completed in a single session without significant perioperative complications. Results: Post-procedure evaluation demonstrated a reduction in pain symptoms and improved eating ability, which positively impacted the patient's nutritional status. Patients with PVL who have intellectual disabilities and communication disorders require a specialized, individualized, and comprehensive approach to dental care. Conclusion: The use of general anesthesia is an effective and safe option for treating various dental infections in patients with limited cooperation, while improving quality of life through pain reduction, improved oral function, and improved nutritional status.